2012
DOI: 10.1007/s00066-012-0128-x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfractionated accelerated radiotherapy with concomitant integrated boost of 70–75 Gy in 5 weeks for advanced head and neck cancer

Abstract: HARTCIB (75 Gy in 5 weeks) is feasible for patients deemed unsuitable for chemoradiation. Acute toxicity was lower than predicted from radiobiological models; duration of dysphagia and confluent mucositis were particularly short. Better conformity of radiotherapy allows the use of more intensive altered fractionation schedules compared with older studies. These results suggest that further dose escalation might be possible when highly conformal techniques (e.g., stereotactic radiotherapy) are used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Similar results are described by Cvek et al; 17 after hyperfractionated accelerated RT with integrated boosts, no 3 or 4 grade toxicity was observed (RTOG/EORTC). Saunders et al 19 described a small, but significant reduction in epidermal and mucosal late adverse effects in the arm treated with accelerated hyperfractionation in comparison with Conv.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Similar results are described by Cvek et al; 17 after hyperfractionated accelerated RT with integrated boosts, no 3 or 4 grade toxicity was observed (RTOG/EORTC). Saunders et al 19 described a small, but significant reduction in epidermal and mucosal late adverse effects in the arm treated with accelerated hyperfractionation in comparison with Conv.…”
Section: Discussionsupporting
confidence: 89%
“…arm. Other authors reported larger percentages of 2-year OS: 55%, 60%, 71% and 74% for hyperfractionated accelerated RT with concomitant integrated boost, 17 hyperfractionated accelerated RT combined with chemotherapy, 15 neoadjuvant chemotherapy followed by concurrent hyperfractionated radiation therapy and sensitizing chemotherapy 9 and hyperfractionated accelerated RT plus cisplatin, 12 respectively. Some authors described an even better 3-year OS: 57% and 60% for split-course hyperfractionated accelerated radiochemotherapy 14 and accelerated hyperfractionated RT concurrent with carboplatin and paclitaxel, 8 respectively (OS 17% in the CHA-CHA arm).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Radiotherapy plays a significant role in the management of head and neck squamous cell carcinoma (HNSCC), either for the definitive radiotherapy or for the post-surgical adjuvant radiation[1], [2]. The mucositis, acute or late xerostomia caused by radiation are the most common toxic effects, which usually interrupt the planned course of treatment[3].…”
Section: Introductionmentioning
confidence: 99%